Comparing the mechanical properties of cold recycled mixture containing coal waste additive and ordinary Portland cement. Issue Volume 17:Issued 3(2016) (15th March 2016) - Modarres, Amir; Ayar, Pooyan
Abstract : Pavement cold recycling is considered as an efficient rehabilitation method, especially in severely distressed roads. Modifier additives have been used for improving the performance of cold recycled mixture (CRM), especially at initial days of curing. In this study, coal waste taken from coal washing plant and its ash produced through the incineration process were used as pozzolanic additives in CRM with bitumen emulsion. To assess the effects of using these additives on mechanical properties of CRM, Marshall stability, indirect tensile strength (ITS), resilient modulus, dynamic creep and fatigue tests were applied. Furthermore, the effect of using these additives on CRM moisture sensitivity was evaluated. Application of coal waste powder improved the mechanical properties of CRM, but it could not exert a positive effect on CRM moisture sensitivity. Thus, coal waste can be used as CRM additive in conditions that moisture damage does not significantly affect the pavement performance. Unlike the coal waste powder using the coal waste ash not only increased the durability of CRM, but also it showed upgrading the mechanical properties. In continue, the mechanical properties of the CRM containing coal waste and its ash were compared with the mix that stabilised with 1% and 2% ordinary Portland cement (OPC). Based on the comparisons, coal waste powder and its ash had comparable effects to OPC. For example, the results of fatigue tests revealed that at higher strain levels of 200 μϵ the fatigue life of the CRM mix containing 7% coal waste and coal waste ash was higher than that of containing 1% and 2% cement. Finally, apart from the several environmental advantages it was concluded that the use of coal waste powder and its ash had technical benefits in cold recycling with bitumen emulsion.